ANALISIS DAN IMPLEMENTASI HONEYPOT MENGGUNAKAN HONEYD SEBAGAI ALAT BANTU PENGUMPULAN INFORMASI AKTIVITAS SERANGAN PADA JARINGAN - Nugroho, Ardianto Setyo; Raharjo, Suwanto; Triyono, Joko (Jurnal Jarkom, 2013)
ABSTRACTÂ A honeypot is a system that is purposely built to be investigated , attacked, or compromised . In general, a honeypot is a computer , data or a network site that looks like part of the network , but actually terisolalsi and monitored . When viewed from the eyes of the hacker would attack , honeypot systems like that deservest to be attacked. One type of honeypot is Honeyd . Honeyd is a low interaction honeypot with types that have a much smaller risk than other types of interactions due to the high interaction honeypot does not directly involve the actual system . In testing this system , implemented on a local network honeypot to try some attacks such as footprinting , DoS , and bruteforce is expected to be one of the information to the administrator of hasillog honeypot in order to make the system more secure . This ,implementation of honeypot can be used as a tool administrators to view activity reports generated Honeyd in order to assist in determining the network security policy .Â Keywords : honeypot , Honeyd , footprinting , Dos , bruteforceÂ